1994
DOI: 10.1007/bf00123667
|View full text |Cite
|
Sign up to set email alerts
|

A fast and efficient method to generate biologically relevant conformations

Abstract: Mutual binding between a ligand of low molecular weight and its macromolecular receptor demands structural complementarity of both species at the recognition site. To predict binding properties of new molecules before synthesis, information about possible conformations of drug molecules at the active site is required, especially if the 3D structure of the receptor is not known. The statistical analysis of small-molecule crystal data allows one to elucidate conformational preferences of molecular fragments and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
122
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(125 citation statements)
references
References 45 publications
1
122
0
Order By: Relevance
“…b Total number of complexes with the specified number of rotatable bonds in test set 1. result. The extensive MINUMBA 45 conformer library used by FlexX to explore conformational space during the incremental build-up procedure may better represent the sulfonamide group. This failure is not inherent in the MD sampling method of CDOCKER, but rather, these results point to a systematic error in the underlying force field for this particular group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…b Total number of complexes with the specified number of rotatable bonds in test set 1. result. The extensive MINUMBA 45 conformer library used by FlexX to explore conformational space during the incremental build-up procedure may better represent the sulfonamide group. This failure is not inherent in the MD sampling method of CDOCKER, but rather, these results point to a systematic error in the underlying force field for this particular group.…”
Section: Discussionmentioning
confidence: 99%
“…Interactions take place for complimentary matches between protein and ligand sites. Ligand flexibility is treated by an incremental build-up method that uses the MINUMBA 45 conformer library to grow ligands during the docking process. Here the FlexX method as implemented in SYBYL 27 was applied to test set 1 using most of the default parameters.…”
Section: Methodsmentioning
confidence: 99%
“…One such study of 80 protein-ligand complexes revealed similar torsion angle distributions for fragments when the bound and unbound distributions were compared. 14,15 Several conformer generation programs employ empirically derived torsion libraries to help ensure that only energetically favorable conformations are produced. The transferability of CSD torsion angle distributions to biologically active ligand conformations is borne out in the success of these programs.…”
Section: Relevance Of Small Molecule Crystal Structure Conformations mentioning
confidence: 99%
“…A conformational analyzer with molecular dynamics and sampling (CAMDAS) is one example of a program to derive compound conformations [31]. At present 3D-QSAR models could be generated by such programs as Catalyst (Accelrys, Inc., San Diego, USA), comparative molecular fi eld analysis (CoMFA) [32], and comparative molecular similarity index analysis (CoMSIA) [33]. These programs generate a hypothetical pharmacophore as a set of descriptors distributed within a 3D space.…”
Section: Ligand-based Prediction System For the Blockade Of Herg Currentmentioning
confidence: 99%